Die maintenance handbook - Smith, David A. (Society of Manufacturing Engineers, 2001)
From the author of the classic reference, Die Design Handbook, Die Maintenance Handbook crystallizes lessons that have been learned through years of scrupulous problem solving in countless shops around the globe. It goes beyond typical solutions to common tool and die problems. It gives effective maintenance strategies, so trouble can be avoided early in the game. Learn how costly die repairs can be avoided when required tasks are applied at scheduled times during the die maintenance process. This book guides the reader through the basics of the die operation, and then prescribes the correct maintenance procedures for each critical task, including those never before put to print.
Includes index.
Keywords: Dies (Metal-working); elektronické knihy; electronic books